Anxiety disorders in patients with infertility - A. N. Sulima; V. V. Stroevsky; A. S. Bakharovskaya (Сибирский научный медицинский журнал, 2025)
The article is devoted to anxiety disorders in patients with infertility. Along with the physical aspects of this condition, many patients are experiencing significant emotional and psychological suffering. Women often experience feelings of loss, guilt, and loneliness. Unsuccessful trying to get pregnant can be a source of constant stress, affecting quality of life and relationships with partners and loved ones. The literature review presents modern data on the classification of infertility, symptoms of anxiety disorder, its etiology, the role of physiological, psychological and social factors, and the diagnosis of anxiety disorder using clinical and psychometric methods. The methods of treatment used are described, including psychopharmacological methods and psychotherapy. Anxiety disorders are a frequent companion of infertility, but they can and should be fought. A comprehensive approach including psychotherapy, medical treatment and support from loved ones helps many women to cope with anxiety and restore psycho-emotional balance.